2020
DOI: 10.1177/1468087419900072
|View full text |Cite
|
Sign up to set email alerts
|

Effect of piston shape design on the scavenging performance and mixture preparation in a two-stroke boosted uniflow scavenged direct injection gasoline engine

Abstract: Compared to a four-stroke engine, the two-stroke engine doubles firing frequency and has favourable power-to-weight or power-to-volume ratio as well as engine downsizing to improve the overall powertrain fuel economy. In order to overcome the shortcomings of the conventional cross-flow or loop scavenged two-stroke engines, a two-stroke boosted uniflow scavenged direct injection gasoline engine was designed and its performance was analysed. In this study, three-dimensional computational fluid dynamics simulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…On the other hand, new engine concepts pursue accomplishing the latest fuel consumption and emissions requirements [9]. Some innovative engine configurations are gasoline 2-stroke direct injection engines [10] and two stroke opposed piston engines [11]. It is this line where this study contributes with a new 2-stroke Rodless Opposed Pistons Engine (2S-ROPE) concept.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, new engine concepts pursue accomplishing the latest fuel consumption and emissions requirements [9]. Some innovative engine configurations are gasoline 2-stroke direct injection engines [10] and two stroke opposed piston engines [11]. It is this line where this study contributes with a new 2-stroke Rodless Opposed Pistons Engine (2S-ROPE) concept.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, Gasoline Direct Injection (GDI) technology has been widely adopted as a common engine configuration and a hot spot on the academia and industry. [30][31][32][33][34][35] In 2005, an advanced technology named dual-injection, which schematic is shown in Figure 2, was commercially applied to SI engines by Toyota. 36 With the combination of GDI and PFI's advantages, dual-injection technology of SI engine has attracted more researchers in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…23][24][25][26][27][28][29] applied ICRC method to practical Port Fuel Injection (PFI) SI engines fuelled with propane under operating conditions of oxygen volume fraction from 40% to 55%. These studies revealed that engine performance under OFC mode could be improved by optimising operating parameters, such as oxygen fraction, water injection, etc.Nowadays, Gasoline Direct Injection (GDI) technology has been widely adopted as a common engine configuration and a hot spot on the academia and industry[30][31][32][33][34][35]. In 2005, an advanced technology named dual-injection, which schematic is shown in Figure2compression ratio and boost level can be achieved due to effective knock suppression.…”
mentioning
confidence: 99%
“…However, few studies have been reported about the implementation of OFC in GDI engines or dual-injection SI engines. However, Gasoline Direct Injection (GDI) technology has become the mainstream of SI engines in academia and industry [27][28][29][30][31][32][33][34][35]. In 2005, an advanced technology named dual-injection was commercially applied to SI engines by Toyota [36].…”
Section: Introductionmentioning
confidence: 99%